Letter from Steve Selig - Steve Selig:::::: (1976)
This October 6, 1976 letter from Steve Selig, Deputy Campaign Director, urges Democratic National Convention delegates to continue supporting the Carter-Mondale campaign. It thanks them for their role in nominating Jimmy Carter and emphasizes the need for their local knowledge and political experience to assist state campaign efforts. The letter asks delegates to contact their state headquarters and contribute in the crucial final days of the election campaign.